(untitled) (Baghdad Science Journal, 2016)
Some coordination complexes of Co(??), Ni(??), Cu(??), Cd(??) and Hg(??) are reacted in ethanol with Schiff base ligand derived from of 2,4,6- trihydroxybenzophenone and 3-aminophenol using microwave irradiation and then reacted with metal salts in ethanol as a solvent in 1:2 ratio (metal: ligand). The ligand [H4L] is characterized by FTIR, UV-Vis, C.H.N, 1H-NMR,13C-NMR, and mass spectra. The metal complexes are characterized by atomic absorption, infrared spectra, electronic spectra, molar conductance, (C.H.N for Ni(??) complex) and magnetic moment measurements. These measurements indicate that the ligand coordinates with metal (??) ion in a tridentate manner through the nitrogen and oxygen atoms of the ligand, octahedral structures are suggested for these complexes. Antibacterial activity of the ligand [H4L] and its complexes are studied against (gram positive) and (gram negative) bacteria [Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus and Bacillus]. The proposed structure of the complexes using the program, Chem office (2006) and the general formula has been given for the prepared ligand complexes K2[M(H2L)2].